Analisis Gaya Belajar Siswa Kelas V pada Mata Pelajaran Bahasa Indonesia - Puspita, Erin Syefa; Azizah, Mira; Rofiatun, Nur; Untari, Mei Fita Asri (Jurnal Likhitaprajna, 2024)
This research aims to analyze based on the Indonesian language learning style of class VA SDN Kalicari 01 for the 2023/2024 academic year. The research method used is descriptive qualitative. The research sample was the VA class of SDN Kalicari 01. The data collection techniques used were observation, distributing questionnaires, and interviews. The results of the analysis determining the most dominant learning style are the visual learning style with a frequency of 13 percentages of 46.43%. The auditory learning style with a frequency of 10 percentages of 35.71%. The learning style that is the least is kinesthetic with a frequency of 5percentage of 17.86%.